Zollman's Four Corners and a Diamond Graphic Organizer as a Solving Strategy in Secondary Mathematics Word Problems - Wong, Cheau Mei; Tengah, Khairul Amilin (International Journal on Emerging Mathematics Education, 2021)
This action research examined the effectiveness of the Zollman's Four Corners and a Diamond graphic organizer as a strategy to improve Year 10 students' performance in mathematics word problems. Quantitative data from twenty-four students from a secondary school in Brunei Darussalam was collected through the use of a pre-test and post-test. Results from the pre-test and post-test were analyzed and it was found that there was a significant difference in students performance before and after introducing the Zollman's Four Corners and a Diamond graphic organizer. A paired sample t-test on the pre-test and post-test showed a significant improvement in students' mean marks, t(23) = -3.415, p = .002. Additionally, it was found that the Zollman's Four Corners and a Diamond graphic organizer is capable of helping students of all abilities and particularly the lower ability students. Hence for this study, the Zollman's Four Corners and a Diamond graphic organizer successfully enhanced the Year 10 students' performance in solving mathematics word problems.